Mengintegrasikan Teknologi Wordwall pada Pembelajaran PAI di Sekolah Dasar Islam Terpadu Permata Mulia - Nurul Faizatus Sholikah (STIKes Ibnu Sina Ajibarang, 2025)
This study focuses on the use of Wordwall technology in Islamic Religious Education (PAI) learning at the elementary school level. Wordwall, as an interactive learning tool, allows teachers to create interesting activities such as quizzes and games that are in accordance with the subject matter. The purpose of this study was to test how effective Wordwall is in increasing student participation, curiosity, and understanding of PAI material that is often considered difficult. The results of the study showed that the use of Wordwall has a positive impact, making students more active, improving their collaboration, and social skills. In addition to making it easier for teachers to evaluate student understanding formatively, Wordwall also helps convey religious values ​​in an interesting and relevant way to technological developments in this digital era.